The Judiciary as an Institution - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2015)
his issue of the Victoria University of Wellington Law Review contains a symposium of student work on the judiciary. This introductory article sets out the circumstances surrounding the preparation of the articles and the course of instruction that preceded them. It also sets out the constitutional background relating to the New Zealand judiciary and introduces the articles themselves. It refers to some changes contained in the Judicature Modernisation Bill that was nearing the end of its parliamentary passage when editing of the symposium was completed.